Pelatihan Manajemen Resiko bagi Pekerja Konstruksi Gudang Bulog Kabupaten Demak (Penyusunan Rencana Keselamatan Konstruksi Pra Desain) - Sutik; Lestari, Fitria Maya; Herdiarti, Etika; Sasmito S, Nuryanto (Faculty of Engineering, Universitas Semarang, 2026)
Risk management is defined as a systematic process that includes planning, organizing, leading, and controlling organizational activities to minimize the likelihood of revenue loss. PT Mustiko Klopo Jati faces challenges related to improving construction risk management practices. The implementation of this activity is carried out in the Bulog Warehouse Construction Project. The objective of this community service program (PKM) is to provide risk management training with a focus on the preparation of the Construction Safety Plan (RKK). This training aims to enhance participants’ knowledge in preparing RKK documents in accordance with the latest regulatory standards. Before the training, 48% of participants had a limited understanding of the RKK preparation process; following the training, the level of understanding among construction practitioners increased to 85%. It is expected that this activity will provide solutions to the identified problems and foster effective collaboration with industry partners, thereby contributing to innovation in the implementation of efficient and appropriate construction practices.